Reactions caused by dentifrices - Cases report and literature review (Research, Society and Development, 2022)
Introduction: Stomatitis and contact dermatitis caused by toothpastes can be related to different components present in the formulations, manifesting immediately after or after a certain time of use of the product. The objective of this study was to report cases of contact reactions caused by the use of a dentifrice in addition to performing a literature review on the subject to clarify the clinical findings presented. Methodology: Case reports and literature review on the main ingredients related to the conditions described. For the analysis of the components of the formulation with the potential to cause the reactions, 25 articles were selected for full reading. Case reports / Results: Two patients presented with intraoral lesions after using the same type of toothpaste for a short period of time. The suspicion was a contact reaction caused by the product and the intervention adopted was the suspension of use. The complete resolution of the picture happened in a few days. After reviewing the literature, it was found that flavorings (cinnamal), anionic detergents (sodium lauryl sulfate), sodium hexametaphosphate (anti-tartar agent) and tin are the main components of the formulation with the potential to cause the reactions presented by the patients. Conclusion: Dentists and physicians must know the ingredients of toothpastes that may be associated with stomatitis and contact dermatitis, so that they can diagnose and replace the product, without compromising the necessary therapeutic benefit.